PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) BERORIENTASI PROBLEM BASED LEARNING (PBL) PADA MATERI SISTEM EKSKRESI UNTUK KELAS XI SMA NEGERI 1 WONOMULYO - Magfirah, Nurul; Afifah, Afifah Huwaida; Fadhilah, Nurul Fadhilah (Hybrid: Jurnal Pendidikan dan Pembelajaran Sains, 2024)
This research is research and development (R&D) which aims to develop problem based learning (PBL) oriented student worksheets (LKPD) on Excretory System material for Class XI/SMA Negeri 1 Wonomulyo. which is valid and practical. The development model used is the ADDIE model consisting of analysis, design, development, implementation and evaluation stages. Data collection was carried out by means of interviews, observation and distribution of questionnaires. Data analysis techniques used were qualitative data analysis and quantitative data analysis. The results of the validity analysis show that the PBL-oriented LKPD on the excretion system material developed by the researcher obtained an average result from media expert validators of 3.70 and material experts 3.80 and the average result obtained from both was 3.75 with a very valid category. . Judging from the practical aspect, the average student response questionnaire was 3.72 in the very practical category. The average response from biology teachers was 3.90, resulting in a very practical category. So it can be concluded that based on the validity of the PBL-oriented LKPD on excretory system material it is valid and based on its practicality it is practical.